Fortifying Defenses: Exploring Innovative Security Strategies to Enhance Resilience and Safeguard IoT Networks from Emerging Threats - Harahap, Ahmad Indra; Bahri, Syaiful; Figna, Harry Pratama (Indonesian Journal of Education And Computer Science, 2025)
The widespread adoption of the Internet of Things (IoT) has brought significant benefits to various sectors, but it has also introduced new challenges in terms of security and privacy. This article aims to elaborate on innovative security strategies that can be applied to enhance the resilience of IoT networks. Firstly, we conduct an in-depth review of the current threats faced by IoT networks, including hacking attacks, software exploits, and data misuse. Next, we introduce a series of innovative security strategies designed to address the identified risks. These strategies include the use of blockchain technology for distributed data security, the implementation of biometric-based authentication for user identification, and the utilization of machine learning for behavior-based attack detection. We also highlight the importance of security integration at every stage of the IoT device lifecycle, from design to implementation, as well as the need for cross-sector collaboration to build a holistic security ecosystem. By combining these strategies, it is expected that IoT networks can become more resilient and capable of addressing increasingly complex security threats in the future.